Fauna Diversity and Bird Community Structure in the Bissoloro Educational Forest, South Sulawesi - Kurniawan, Hendra; Marpaung, Sutan Sahala Muda; Oktaviani, Eva; Syah, Firman; Hendra Kurniawan (Jurnal Pijar Mipa, 2025)
The Bissoloro Educational Forest, covering an area of 75.12 hectares in Gowa Regency, South Sulawesi, serves as a natural research site under the stewardship of Muhammadiyah University of Makassar. Although the forest holds considerable ecological value, comprehensive and systematic data on its faunal diversity are still limited. This study was conducted to explore and evaluate the composition, richness, and community structure of fauna within the area, focusing on three major groups: mammals, reptiles, and birds. Data collection for mammals and reptiles was conducted through both direct sightings and indirect indicators, while avian data were obtained using a 1,700-meter line transect with 17 observation points over a three-day survey period. A total of 39 faunal species were recorded, comprising 4 mammal species, 10 reptile species, and 25 bird species. Among the bird species, Pycnonotus aurigaster was identified as the most dominant, with the highest Importance Value Index (INP) of 38.19%, supported by a relative frequency of 19.61% and relative dominance of 18.58%. The overall bird community diversity, as measured by the Shannon-Wiener index (H'), was 2.59, reflecting a moderate level of biodiversity. The occurrence of endemic and protected species, including top predators and nectar-feeding birds, indicates that essential ecological functions such as pollination and food web dynamics are still maintained. These results highlight the ecological importance of the Bissoloro Educational Forest and its role as a vital site for biodiversity conservation, environmental education, and long-term ecological monitoring in alignment with the Merdeka Belajar Kampus Merdeka (MBKM) framework.